Consumer Purchase Intention towards Organic Foods - Shrestha, Sajeeb Kumar (Management Dynamics, 2020)
This research tries to measure consumer purchase intention toward organic foods. The descriptive and causal research design was used. Primary cross-section data were collected by administering structured questionnaires. Two-hundred responses were collected. The convenience sampling method was used. The PLS-SEM tool was used to test the psychometric and econometric dimensions of the proposed model. This research confirmed that environmental concern, trust, and availability were the important predictor for motivating organic food purchase intention. Health concern and awareness were not supported for organic food purchase intention. Marketers have to make their organic food easily available in the markets with a view of health and environmental consciousness to generate trust.